2008
DOI: 10.1210/jc.2007-1419
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and Radiological Studies in Patients with Molecularly Confirmed CHARGE Syndrome

Abstract: We suggest that hypogonadism, GH deficiency, and hypothyroidism could be possible endocrinological defects in patients with CHD7 mutations and that olfactory bulb hypoplasia as well as semicircular canal aplasia should be considered as a major sign for CHARGE syndrome and recommend a computed tomography scan of the temporal bone and magnetic resonance imaging study of the olfactory bulb region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 17 publications
2
60
1
Order By: Relevance
“…However, our series was biased, and we analyzed only a small number of patients with this syndrome because patients with CHARGE syndrome and CHD7 mutations were more likely to undergo imaging. 19 Thus, additional studies of the incidence and severity of CHARGE syndrome without CHD7 mutations are mandatory; however, we tentatively concluded that routine assessment of the basiocciput in patients with CHARGE syndrome is helpful to exclude potentially life-threatening basilar invagination regardless of the presence or absence of CHD7 mutations.…”
Section: (ϫ35)mentioning
confidence: 79%
“…However, our series was biased, and we analyzed only a small number of patients with this syndrome because patients with CHARGE syndrome and CHD7 mutations were more likely to undergo imaging. 19 Thus, additional studies of the incidence and severity of CHARGE syndrome without CHD7 mutations are mandatory; however, we tentatively concluded that routine assessment of the basiocciput in patients with CHARGE syndrome is helpful to exclude potentially life-threatening basilar invagination regardless of the presence or absence of CHD7 mutations.…”
Section: (ϫ35)mentioning
confidence: 79%
“…There is a higher percentage of stop codons in our cohort than in the published literature (52.7% vs. 35.4%). Of 189 published mutations, there were 35.4% stop mutations, 33.3% frameshifts, 7%-15% splicing mutations, 6%-13% missense mutations, and 3% large deletion/duplications (Vissers et al, 2004;Felix et al, 2006;Jongmans et al, 2006;Lalani et al, 2006;Sanlaville et al, 2006;Aramaki et al, 2007;Vuorela et al, 2007;Asakura et al, 2008;Bergman et al, 2008;Gennery et al, 2008;Wincent et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…DNA sequencing detects CHD7 mutations in *58%-64% of patients clinically diagnosed with CHARGE syndrome (Vissers et al, 2004;Jongmans et al, 2006;Lalani et al, 2006). Of the CHD7 mutations reported thus far, *70% are nonsense or frameshift, 6%-13% are missense, and 7%-15% are splice site mutations (Vissers et al, 2004;Felix et al, 2006;Jongmans et al, 2006;Lalani et al, 2006;Sanlaville et al, 2006;Aramaki et al, 2007;Vuorela et al, 2007;Asakura et al, 2008;Bergman et al, 2008;Gennery et al, 2008;Wincent et al, 2008). Partial and whole gene deletions or duplications are rare, accounting for 3%-4% of pathogenic CHD7 mutations (Aramaki et al, 2006;Vuorela et al, 2007;Bergman et al, 2008;Wincent et al, 2008).…”
mentioning
confidence: 99%
“…In this article, we give an overview of all CHD7 missense variants reported in the literature before 15 June 2011 [Asakura et al, 2008;Bartels et al, 2010;Bergman et al, 2011a, b;Dauber et al, 2010;De Arriba Munoz et al, 2011;Delahaye et al, 2007;Felix et al, 2006;Feret et al, 2010;Fujita et al, 2009;Gao et al, 2007;Holak et al, 2008;Jongmans et al, 2006Jongmans et al, , 2008Jongmans et al, , 2009Kim et al, 2008;Lalani et al, 2006;Pauli et al, 2012;Vissers et al, 2004;Vuorela et al, 2007;Wessels et al, 2010;Wincent et al, 2008] and the variants that were reported in the NCBI Single Nucleotide Polymorphism database (http://www.ncbi.nlm.nih.gov/SNP, dbSNP build 132) with frequency data (n = 104, Supp. Table S1).…”
Section: Inclusion Of Chd7 Missense Variantsmentioning
confidence: 99%